Lost in Shangri-la [compact disc, unabridged] : a true story of survival, adventure, and the most incredible rescue mission of World War II - Zuckoff, Mitchell (Books on Tape, 2011)
Award-winning former Boston Globe reporter Mitchell Zuckoff chronicles the untold story of an extraordinary World War II rescue mission, in which a plane crash in the South Pacific plunged a trio of U.S. military personnel into the jungle-clad land of New Guinea.